A multi-mechanical nonlinear fibre beam-column model for corroded columns. Issue 2 (11th April 2016) - Kashani, Mohammad M; Lowes, Laura N; Crewe, Adam J; Alexander, Nicholas A
Abstract : Purpose: – A new modelling technique is developed to model the nonlinear behaviour of corrosion damaged reinforced concrete (RC) bridge piers subject to cyclic loading. The model employs a nonlinear beam-column element with multi-mechanical fibre sections using OpenSees. The nonlinear uniaxial material models used in the fibre sections account for the effect of corrosion damage on vertical reinforcing, cracked cover concrete due to corrosion of vertical bars and damaged confined concrete due to corrosion of horizontal tie reinforcement. An advance material model is used to simulate the nonlinear behaviour of the vertical reinforcing bars that accounts for combined impact of inelastic buckling and low-cycle fatigue degradation. The basic uncorroded model is verified by comparison of the computation and observed response of RC columns with uncorroded reinforcement. This model is used in an exploration study of recently tested RC components to investigate the impact of different corrosion models on the inelastic response of corrosion damaged RC columns. The paper aims to discuss these issues. Design/methodology/approach: – A series of pushover and cyclic analyses on a hypothetical corroded RC columns are conducted. The impact of corrosion on reinforcing steel and concrete is modelled. The influence of cyclic degradation due to low-cycle fatigue is also modelled. Findings: – Corrosion has a more significant impact on ductility loss of RC columns than the strength loss plastic moment capacity It was found that the flexural failure is initiated by buckling of vertical bars and crushing of core concrete which then followed by fracture of bars in tension. The analyses results showed that for seismic performance and evaluation of existing corroded bridges monotonic pushover analysis is insufficient. The cyclic degradation due to low-cycle fatigue has a significant influence on the response of corroded RC columns. Originality/value: – The finite element developed in this paper is the most comprehensive model to date that is able to capture the onlinear behaviour of corroded RC columns under cyclic loading up to complete collapse.